1986
DOI: 10.1038/ki.1986.215
|View full text |Cite
|
Sign up to set email alerts
|

Chronic effects of dietary protein in the rat with intact and reduced renal mass

Abstract: The chronic effects of dietary protein on renal structure and function were studied in rats with normal and reduced renal mass. Control rats with two kidneys were compared with unilaterally nephrectomized rats, and with one and one-third nephrectomized rats obtained by unilateral nephrectomy and infarction of one-third of the remaining kidney. Rats at each level of renal mass were maintained on chow containing either 6% or 40% protein content. Separate cohorts of rats were studied four and eight months after a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
163
2
3

Year Published

1990
1990
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 321 publications
(172 citation statements)
references
References 23 publications
4
163
2
3
Order By: Relevance
“…In rats with experimental nephritis or 1-sided nephrectomy, glomerular hypertension appears without hypertension. 21,22,25,26 The glomerular pressure in our patients with normal to high-normal pressure may be higher than that in our patients with optimal pressure. We calculated the glomerular pressure in the patients of this study by the method used in our previous study.…”
Section: Discussionmentioning
confidence: 71%
“…In rats with experimental nephritis or 1-sided nephrectomy, glomerular hypertension appears without hypertension. 21,22,25,26 The glomerular pressure in our patients with normal to high-normal pressure may be higher than that in our patients with optimal pressure. We calculated the glomerular pressure in the patients of this study by the method used in our previous study.…”
Section: Discussionmentioning
confidence: 71%
“…Disturbances in renal hemodynamics were among the earliest abnormalities observed when protein intake was increased (5). In physiologic studies that were performed with classic micropuncture techniques, rats that were fed a high-protein diet were found to have high GFR as a result of increased glomerular perfusion and pressure (6). Persistent glomerular hypertension was shown to mediate progressive renal injury in rat models of diabetes and reduced renal mass (6,7).…”
Section: Experimental Modelsmentioning
confidence: 99%
“…Studies in CRF patients (randomized trial or not) reported that starting a restriction of dietary protein and phosphate early in the course of CRF has a considerable influence on the rate of progression of this disease (Mitch, 1991 ;Levey et al, 1996aLevey et al, , 1996bWilliam & Maroni, 1998 ;Mackenzie & Brenner, 1998, Garneata & Mircescu, 2010Kalista-Richards, 2011;Fouque et al, 2011a). In experimental models, dietary protein restriction reduces the load of N metabolism end-products for excretion, limits the adaptive changes in remnant nephrons, and slows the tendency to renal disease progression (Hostetter, 1986). Despite the unambiguous support from experimental studies, the conclusive results are often regarded as unconvincing and as they do not meet strict statistical rules (Gretz & Strauch, 1986;Garneata & Mircescu, 2010).…”
Section: Present Dietary Approach To Treat the Patient With Chronic Rmentioning
confidence: 99%